Neuro architectural design. (18th December 2017) - Hemeida, Fahd Abd ElAziz; Mostafa, Hamad Hassan
Abstract: The relationship between the human mind and creativity in design is always confusing where it is interspersed with a lot of consequences that might hinder the design process. Since the beginning of creation, the design is constantly evolving. However, architectural science has lately witnessed tremendous boom in the use of computers to express complex geometric shapes that were difficult to move from the mind to the drawings. The design process relies in all stages of the transfer on signals from the right lobes of the brain to the nerves and then to the hand to carry whatever information that is reached by the mind to graphics. With the development of science, design three-dimensional programs have begun to rely on coordinates instead of the two-dimensional drawing and turn it into perspective. Therefore, it is possible to imagine that there could be a direct connection between the waves of the human mind and programs in order to design the coordinates of the cell is to be the future design codes.